Moisture Control in Your Home, Part 1: The Basics - Hyun-Jeong Lee; Virginia Peart (EDIS)
FCS3256, a 3-page fact sheet by Hyun-Jeong Lee and Virginia Peart, explains how mold and mildew growth in the home can be prevented by controlling and eliminating indoor moisture and gives practical tips on how to keep your home dry and mildew-free. This publication combines, updates, and supersedes FCS3042, FCS3211, FCS3212, FCS3213, FCS3239, FCS3244, and FCS3245. Published by the UF Department of Family, Youth and Community Sciences, January 2007.